Web Site Media Relations: A New Direction for Agricultural Public Relations Professionals - Amanda Ruth; Denise Bortree; Ross Ford; Sandra Braun; Kelly Flowers (Journal of Applied Communications, 2005)
Agricultural public relations practitioners and communicators face a challenge in following the current trend in Web-based media information dissemination. Most agricultural organizations serve a traditional clientele that prefer conventional media as a source of news and information. This may result in many agricultural communicators overlooking the information needs of the media, which in turn could be a reason for the media to neglect agricultural news. A content analysis was conducted of Web sites created and maintained by all major Florida agricultural commodity organizations to determine the percentage of Florida Agricultural Web sites that provide media information, the location of media information within the Web sites, and the type of media information provided. Results indicated that the primary objective of these agricultural commodity Web sites appears to be to provide an internal communication mechanism for members. It was evident that the agricultural sites are not created with the needs of journalists or members of the media as a priority. Certainly, it is positive that there are press releases, feature stories, and logo graphics available on numerous Web sites; however, many releases were outdated and many elements of a good pressroom were absent.